Structure and thermodynamics of a multimeric cavitand assembly - Aakeröy, Christer B.; Chopade, Prashant D.; Quinn, Colette F.; Desper, John (My University, 2014)
A set of COOH···N(pyridine) 5 hydrogen bonds have been utilized in the targeted synthesis of a cavitand-based assembly. A cavitand appended with four pyridyl groups was synthesized from a Suzuki coupling of a tetrabromocavitand and 3-pyridyl boronic acid. The product resulting from the reaction between the tetra-pyridyl cavitand and 4-nitrobenzoic acid was investigated in solution using isothermal titration calorimetry (ITC) under equilibrium conditions, and in the solid state through single-crystal X-ray diffraction and infrared spectroscopy. The results show that the targeted pentameric hydrogen-bonded architecture was isolated in the solid-state, and the infrared spectroscopy confirm the presence of COOH···N(py) interactions. The same assembly, with a 1:4 cavitand:acid stoichiometry, is also present in solution in acetonitrile and the enthalpy of binding for this reaction is approximately -45 kJ/mol.
Keywords: Multimeric cavitand assembly; Cavitand; X-ray diffraction; Infrared spectroscopy